The Influence of Job Satisfaction and Organizational Commitment on Employee Performance Through Organizational Citizenship Behavior (OCB) as an Intervening Variable at PT. Bank Rakyat Indonesia (Persero) Iskandar Muda Branch - Ginting, Rini Troelin; Lumbanraja, Prihatin; Sirojuzilam, Sirojuzilam (International Journal of Business and Applied Economics, 2025)
This study examines the relationship between organizational citizenship behavior (OCB), job satisfaction, and organizational commitment as they relate to employee performance at the Iskandar Muda branch of PT. Bank Rakyat Indonesia. Results from a path study of 92 workers show that OCB is strongly affected by factors including job satisfaction and organizational commitment. Not only that, but employee performance is positively affected by both of these criteria. Organizational citizenship behavior (OCB) acts as a go-between for three factors: work happiness, loyalty to the company, and productivity.